2019
DOI: 10.1353/cp.2019.0004
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Well-Being and Development: Connections to Large-Scale Mining and Tourism in the Pacific

Abstract: Growth in the South Pacific tourism industry along with rising demand for mineral resources has led to increasing numbers of multinational corporations operating across the Pacific, particularly in the tourism and mining sectors. Multinational hotels and large-scale mining activities are now frequently located near communities with high development demands, and extractive industries are additionally found in very remote and rural locations. Both hotels and mines rely on local communities for access to resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…Mauss used the M aori concept of 'hau taonga' to illustrate this, arguing that the gift had a spiritual force, seeking to return to its original owner or place of origin. While this is a clear example of the appropriation and distortion of an indigenous concept to serve Eurocentric scholarly purposes and it is beyond the scope of this paper to examine the accuracy of Mauss' use of indigenous concepts (for an examination of this from a M aori perspective, see Stewart, 2017), gift exchange remains an essential cultural tradition in the Pacific region, where the processes of gift-giving and reciprocity are cornerstones of culture and community (Funaki, 2016(Funaki, , 2018Richardson, Hughes, McLennan, & Meo-Sewabu, 2019). A giving philosophy is woven into the Pacific mind-set, and is reflected in cultural traditions and values including the importance of maintaining generosity within the community, knowing one's status within the social structure, and using one's full resources to demonstrate obligations to others (Funaki, 2016).…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mauss used the M aori concept of 'hau taonga' to illustrate this, arguing that the gift had a spiritual force, seeking to return to its original owner or place of origin. While this is a clear example of the appropriation and distortion of an indigenous concept to serve Eurocentric scholarly purposes and it is beyond the scope of this paper to examine the accuracy of Mauss' use of indigenous concepts (for an examination of this from a M aori perspective, see Stewart, 2017), gift exchange remains an essential cultural tradition in the Pacific region, where the processes of gift-giving and reciprocity are cornerstones of culture and community (Funaki, 2016(Funaki, , 2018Richardson, Hughes, McLennan, & Meo-Sewabu, 2019). A giving philosophy is woven into the Pacific mind-set, and is reflected in cultural traditions and values including the importance of maintaining generosity within the community, knowing one's status within the social structure, and using one's full resources to demonstrate obligations to others (Funaki, 2016).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…A giving philosophy is woven into the Pacific mind-set, and is reflected in cultural traditions and values including the importance of maintaining generosity within the community, knowing one's status within the social structure, and using one's full resources to demonstrate obligations to others (Funaki, 2016). As this paper will argue, gift theory also intersects with Pacific approaches to well-being and development through an emphasis on relationships and interconnectedness, and the importance placed on supporting agency and dignity (Funaki, 2016;Richardson et al, 2019). As a theory of solidarity with roots in the Pacific context, gift theory therefore provides a useful lens to examine the relationships between Pacific Island Countries (PICs) and development partners.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Young-Leslie and Moore [30] studied the Tongan concept of happiness using a standardized well-being questionnaire and found that positive emotions were significantly associated with traditional social functioning and kinship obligations. Further, two linguistic studies indicate indirectly that the basic conceptualization of happiness in Indigenous Pacific populations may be embedded in a collective interdependence with others [33,34]. Ethnographic analyses of well-being in Pacific Island countries through language and cultural traditions have emphasized that supporting the needs of others is central to individual happiness values and that well-being has indigenous knowledge at its core [33,34].…”
Section: Happiness In the Pacific Islands Region And Fijimentioning
confidence: 99%
“…Further, two linguistic studies indicate indirectly that the basic conceptualization of happiness in Indigenous Pacific populations may be embedded in a collective interdependence with others [33,34]. Ethnographic analyses of well-being in Pacific Island countries through language and cultural traditions have emphasized that supporting the needs of others is central to individual happiness values and that well-being has indigenous knowledge at its core [33,34]. Further, words connected with happiness in the native Fijian language such as Bula Taucoko and Sautu (both: Well-being) inculcate the fulfillment of communal obligations and supportiveness as the foundation to individual happiness [34].…”
Section: Happiness In the Pacific Islands Region And Fijimentioning
confidence: 99%
“…Richardson et al (2019) argue that notions of well-being in Oceania are shaped by an outlook that is significantly different to Western understandings of well-being. Drawing on commonalities from the work ofGegeo (1998),Nabobo-Baba (2006),Cox (2006) andMeo- Sewabu (2015),Richardson et al (2019) argue that well-being in Oceania values a holistic understanding:"Together these concepts of well-being encompass shared ideas about fulfilling communal obligations, prioritizing collective well-being, and practicing reciprocityall sustained by local knowledge. Well-being is fulfilled through meeting spiritual, psychological, and physical needs and is underpinned by cultural values such as kin love and kindness, sharing and hospitality, and honesty and humility."…”
mentioning
confidence: 89%